Lexical Classes and the Conative Construction in Old English - Acevedo, Eulalia (Studia Anglica Posnaniensia, 2009)
This paper is concerned with the description of the event structure and the meaning components that motivate the realization of the conative construction within some canonical Old English verb classes. In the same line as the latest proposals framed within the Lexical Constructional Model, this kind of description is intended to evidence the essential role of semantic features that are not necessarily realized in the syntax and thus help elucidate and comprehend lexical-constructional processes. Besides, this work seeks to establish adequate criteria to identify the conative construction and provides insights into the distribution of diathetic alternations associated to the conative construction in Old English.